Peran Employee Resilience dalam Konteks Job Insecurity - Cicilya, Hanny (IAI Nasional Laa Roiba Bogor, 2025)
Policy changes in the civil servants aim to create a better, more efficient, effective, transparent, and responsive government that aligns with societal needs. These changes have wide-ranging implications for individual civil servants, government organizations, and society at large. For individual civil servants, it is necessary to adjust themselves to new policies that can have an effect on job security and changes in work patterns. The purpose of this study is to analyze how job insecurity and employee resilience affect civil servants’ performance and how the influence of job insecurity on employee resilience. The research employs a quantitative method (explanatory research). The study population consists of 351 civil servants in Kotawaringin Barat Regency affected by bureaucratic simplification policies, with data collected from 123 respondents through questionnaires. The data analysis technique used is statistical analysis with the PLS-SEM method. The result of this research show that job insecurity does not have a significant effect on human resource performance. However, employee resilience has a positive and significant influence on human resource performance and job insecurity has a positive and significant influence on employee resilience. job insecurity does not significantly affect human resource performance.